Understanding State-Level Advocacy: A Guide for Hearing Healthcare Professionals - Roman, Aaron M. (Seminars in Hearing, 2022)
Advocacy is a core component of moving the hearing healthcare environment forward to optimize patient care and allow providers to work to the full extent of their scope of practice. Despite its importance, advocacy, particularly at the level of state governments, can present to many as a daunting, sometimes futile, task. The purpose of this article is to describe advocating at the state level for hearing healthcare service providers. This article will discuss considerations for audiology practitioners interested in state-level advocacy, including variations in state government organization, benefits and barriers to state advocacy, and state-level issues that affect practitioners.
Keywords: healthcare advocacy; state advocacy; government relations